In-situ phase evolution of multi-component boride to high-entropy ceramic upon ultra-high temperature ablation. Issue 4 (April 2023) - Guo, Lingxiang; Wang, Yuqi; Liu, Bing; Zhang, Yuyu; Tang, Ying; Li, Hongbin; Sun, Jia
Abstract: Multi-component boride (Hf0.5 Zr0.5 )B2 -SmB6 -ErB4 -YB6 (HZRB) utilized as a coating on SiC-coated carbon/carbon (C/C) composite was prepared by supersonic atmosphere plasma spraying. In-situ phase evolution of HZRB into (Hf0.2 Zr0.2 Sm0.2 Er0.2 Y0.2 )O2-δ high-entropy oxide (HEO) was investigated after oxyacetylene ablation for 120 s. The first-principles calculations were applied to analyze the in-situ formation mechanism of HEO. The mixing Gibbs free energy change ( ∆ G mix ) of HEO was calculated to be negative at 2573 K, indicating that the HEO can be generated upon the ablation temperature. Due to the lower Gibbs free energy change of reaction ( ∆ R G m ), (Hf0.5 Zr0.5 )B2 will be oxidized to generate HfO2 firstly, and other elements dissolved into the HfO2 lattice to form HEO. The solution energies of Zr, Sm, Er and Y atoms are − 0.01, 6.28, 8.55 and 4.46 eV/atom, and corresponding solution reactions possess negative ∆ R G m, indicating the possible solution sequence of these elements is Zr > Y > Sm > Er.